A Redox-Mediator-Integrated Flexible Micro-Supercapacitor with Improved Energy Storage Capability and Suppressed Self-Discharge Rate - Sung Min Wi; Jihong Kim; Suok Lee; Yu-Rim Choi; Sung Hoon Kim; Jong Bae Park; Younghyun Cho; Wook Ahn; A-Rang Jang; John Hong; Young-Woo Lee (Nanomaterials, 2021)
To effectively improve the energy density and reduce the self-discharging rate of micro-supercapacitors, an advanced strategy is required. In this study, we developed a hydroquinone (HQ)-based polymer-gel electrolyte (HQ-gel) for micro-supercapacitors. The introduced HQ redox mediators (HQ-RMs) in the gel electrolyte composites underwent additional Faradaic redox reactions and synergistically increased the overall energy density of the micro-supercapacitors. Moreover, the HQ-RMs in the gel electrolyte weakened the self-discharging behavior by providing a strong binding attachment of charged ions on the porous graphitized carbon electrodes after the redox reactions. The micro-supercapacitors with HQ gel (HQ-MSCs) showed excellent energy storage performance, including a high energy volumetric capacitance of 255 mF cm−3 at a current of 1 µA, which is 2.7 times higher than the micro-supercapacitors based on bare-gel electrolyte composites without HQ-RMs (b-MSCs). The HQ-MSCs showed comparatively low self-discharging behavior with an open circuit potential drop of 37% compared to the b-MSCs with an open circuit potential drop of 60% after 2000 s. The assembled HQ-MSCs exhibited high mechanical flexibility over the applied external tensile and compressive strains. Additionally, the HQ-MSCs show the adequate circuit compatibility within series and parallel connections and the good cycling performance of capacitance retention of 95% after 3000 cycles.